The impact of childhood sexual interaction on current psychological functioning in a male forensic population - Rees, Neil David (1998)
Little research attention has been paid to forensic populations of male survivors of childhood sexual abuse (CSA), where it is understood that prevalence rates are high. This study aimed to survey a sample of 40 men in a maximum security hospital who had experienced childhood sexual interaction (CSI). The study profiled the psychological functioning of the sample through a number of standardised measures and a semi-structured interview. In addition, the meanings that the men attached to their childhood sexual experiences,t heir 'constructions' of them, were also examined, along with their self-report of distress related to these experiences. The limited research conducted with male survivors suggests that men tend to construct CSI in more positive or neutral terms than female survivors, and are less likely to report distress related to the experience. However, men's experiences of CSI have still shown similar levels of association with psychological symptomatology in adulthood. This apparent discrepancy has been understood in terms of male socialisation. The predictions that the men in this sample would show high levels of psychological symptomatology, which would be associated with the characteristics of CSI, and that the majority of them would describe positive or neutral constructions of CSI, and would tend to report no distress related to their experiences, were supported in this study. The implications of these findings are discussed. Overall, it is stressed that in order to fully understand the impact of CSA on males, and to provide appropriate approaches to interventions, a fuller appreciation of the role of male socialisation must be achieved